Petunjuk al-Qur’an tentang Instrumen Perekat Rumah Tangga - Ahmad Sekhu (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
Islamic rules are implied through the Qur'an and the hadith of the Prophet. as guidelines and rules for the happiness and safety of mankind in the world and in the hereafter shows that Islam is a religion revealed for human happiness. One of the rules conveyed by the Koran is various instruments to provide a guarantee of happiness in domestic life. It is certain, of course, that humans crave a harmonious, peaceful, happy, and loving family in life in the world to the hereafter. From the family were born great and qualified generations, Salih and Salihah who were able to deliver glory to everyone around him. This article contains household adhesive instruments as hinted by the Qur'an and the hadith of the Prophet Muhammad. as a mubayyin of the Qur'an.